Seismic behavior of precast RC frame equipped with replaceable mechanical plastic hinges - Ozkaynak, Hasan; Soydan, Cihan; Surmeli, Melih; Senol, Erkan; Saruhan, Hakan; Yuksel, Ercan (Techno-Press, 2025)
This paper introduces a precast concrete (PC) frame equipped with replaceable Jacketed Fuse--Type Mechanical Connectors (J-FTMC), referred to as mechanical plastic hinges. The connector is a very effective tool as it allows for reliable on--site assembly of the PC system. The proposed connection can control structural behavior and specifically designed to concentrate seismic--induced damage that may occur during a credible earthquake. J-FTMC is currently recommended for use in beam--to--column connections to take advantage of energy dissipation, where relatively large rotation and plastic deformations are expected in PC frames. The earthquake--induced energy is dissipated within the mechanical plastic hinges owing to its strong post--yielding behavior. A quasi--static test was conducted in the laboratory on a nearly half--scale one--bay, two-story PC frame with mechanical plastic hinges to evaluate its seismic behavior. The contribution of the proposed mechanical plastic hinge was investigated in terms of energy dissipation, damping, ductility, stiffness and strength degradation, self--centering capability, and failure modes. Test results concluded that plastic deformations were primarily concentrated at J-FTMCs with minimal damage observed in the beams and columns. The connectors exhibited excellent replaceability, as they were easily disassembled following the test. The frame achieved yield, and ultimate drifts were observed as 1% and 5% respectively with a maximum strength decrement of only 10% at 5% drift level. A pivot hysteretic type macro--model was generated to replicate the experimental results by assigning a group of equivalent spring elements. The numerical simulation results are in good agreement with the experiment results validating the effectiveness of the proposed modeling approach.
Keywords: energy dissipation; fuse type connector; plastic hinge; precast concrete frame; replaceable connection; seismic performance